Does Chicago's Tax Increment Financing (TIF) Programme Pass the 'But-for' Test? Job Creation and Economic Development Impacts Using Time-series Data. (March 2014) - Lester, T. William
Chicago uses tax increment financing (TIF) to promote economic development to a greater extent than any other large American city. This paper conducts a comprehensive assessment of the effectiveness of Chicago's TIF programme in creating economic opportunities and catalysing real estate investments at the neighbourhood scale. This paper uses a unique panel dataset at the block-group level to analyse the impact of TIF designation and investments on employment change, business creation and building permit activity. After controlling for potential selection bias in TIF assignment, this paper shows that TIF ultimately fails the 'but-for' test and shows no evidence of increasing tangible economic development benefits for local residents. Implications for policy are considered.